Bringing imperialism back in: for an anthropology against empire in the twenty-first century - Campbell, Stephen (2024)
What can a critical analysis of imperialist political economy offer the decolonial turn in the contemporary social sciences? How might revisiting “classic” anti-imperialist thought and politics from the global South push scholars and activists to envision a more revolutionary decolonization? And how, in our discipline’s history, have anthropologists variously opposed or been complicit with the workings of imperialist power? In this article, and in the special issue of Dialectical Anthropology that this article introduces, we engage these questions with a call to bring imperialism “back in” to anthropological research and analysis. Our proposal, however, is not simply for an anthropology of empire, but for an anthropology against empire—a project, that is, not solely of interpreting imperialism, but of aiding its abolition.